Redox chemistry of molybdenum in natural waters and its involvement in biological evolution - Wang, Deli (Frontiers in Microbiology, 2012)
The transition element molybdenum (Mo) possesses diverse valances (+II to +VI), and is involved in forming cofactors in more than 60 enzymes in biology. Redox switching of the element in these enzymes catalyzes a series of metabolic reactions in both prokaryotes and eukaryotes, and the element therefore plays a fundamental role in the global carbon, nitrogen, and sulfur cycling. In the present oxygenated waters, oxidized Mo(VI) predominates thermodynamically, whilst reduced Mo species are mainly confined within specific niches including cytoplasm. Only recently has the reduced Mo(V) been separated from Mo(VI) in sulfidic mats and even in some reducing waters. Given the presence of reduced Mo(V) in contemporary anaerobic habitats, it seems that reduced Mo species were present in the ancient reducing ocean (probably under both ferrigenous and sulfidic conditions), prompting the involvement of Mo in enzymes including nitrogenase and nitrate reductase. During the global transition to oxic conditions, reduced Mo species were constrained to specific anaerobic habitats, and efficient uptake systems of oxidized Mo(VI) became a selective advantage both for prokaryotic and eukaryotic cells. Some prokaryotes are still able to directly utilize reduced Mo if any exists in ambient environments. In total, this mini-review describes the redox chemistry and biogeochemistry of Mo over the Earth’s history.